THE SEISMICITY MIGRATION STUDY BASED ON SPACE-TIME DIAGRAMS - E. A. Levina; V. V. Ruzhich (Геодинамика и тектонофизика, 2015)
Seismicity migration is studied by a new method based on space-time diagrams and a combination of cluster and regression analyses. Data from the global and Baikal regional earthquake catalogues are analysed with the application of the specially designed geographic information system (GIS) in order to establish parameters and mechanisms of seismicity migration in space and time. We study the migration of seismic events in the following geostructural systems: the Baikal rift zone (BRZ), the area between BRZ and the Indo-Eurasian interplate collision zone, the area between BRZ and the West-Pacific seismic foci Benoiff zone, and two segments of the Middle Atlantic ridge.As evidenced by the obtained results, studying regimes of seismic migration provides for analyses of space-time distribution of seismic energy in the fault-block structure of the lithosphere and facilitates more detailed studies of the origin of deformation waves and mechanisms of the seismotectonic regime of the Earth. Forward (from the equator) and backward (towards the equator) migration of seismic events are established in all the regions under study. It is assumed that this phenomenon may result from regular changes of the polar compression of the Earth due to variations of its rotation regime. Besides, it is revealed that energy clusters of migration are regularly generated, and the regularity may be related to the 11-year cycle of the solar activity which impacts the seismic regime. We discuss the need to study the interference of wave deformations in the lithosphere which are initiated by several external energy sources. It is proposed to consider the regimes of planetary seismicity migration as a reflection of redistribution of endogenic (primarily heat) energy of the Earth during the destruction of its lithospheric shell under the impacts of cosmogenic factors via triggering mechansms. With reference to our positive experiences of applying the proposed concept to BRZ, we consider possibilities of using the seismicity migration data for prediction of earthquakes in the planetary and regional scales.